Clinical diagnostic significance of 14-3-3η protein, high-mobility group box-1, anti-cyclic citrullinated peptide antibodies, anti-mutated citrullinated vimentin antibodies and rheumatoid factor in rheumatoid arthritis. Issue 1 (2nd January 2020) - Huang, J; Zeng, T; Zhang, X; Tian, Y; Wu, Y; Yu, J; Pei, Z; Liu, Y; Hu, T; Tan, L
ABSTRACT: Introduction : Circulating markers of rheumatoid arthritis (RA) include the 14–3-3η protein, high-mobility group box-1 (HMGB1), anti-cyclic citrullinated peptide (anti-CCP) antibodies, anti-mutated citrullinated vimentin (anti-MCV) antibodies and rheumatoid factor (RF). We set out to determine which two markers in combination provided best discriminatory power for this disease. Methods : We recruited 108 RA patients, 102 non-RA patients (SLE, AS, Sjogren's syndrome, MCTD) and 90 healthy controls. Sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio, negative likelihood ratio and the Youden index of each analyte were calculated and binary logistic regression analysis and receiver operating characteristic (ROC) curve were performed to evaluate their diagnostic value for RA alone and in paired combination. Results : As expected, all markers were elevated in RA patients ( P < 0.05). Binary logistic regression analysis showed that 14–3-3η had the highest odds ratio (95% CI) at 2.4 (1.9–2.8). Anti-CCP and anti-MCV had the highest areas under the curves [AUC (95% CI)] at 0.85 (0.78–0.90) and 0.85 (0.78–0.91) respectively (both P < 0.001). In serial detection (one marker followed by another), no combination had a Youden index >0.6. In parallel analysis (both considered together) several combinations had a Youden index >0.7, of which the highest (0.78) was anti-CCP with anti-MCV, with a sensitivity of 93.3% and specificity of 84.7%. Conclusions : Despite individual increases in serum 14–3-3η, HMGB1, anti-CCP, anti-MCV and RF, the combination of anti-CCP and anti-MCV might be of great help for diagnostic in RA, and so should be considered as routine tests for this disease.